Design Of Railway Station Facilities Based On Contemporary Architecture - Sarajar, Kivly E.; Muhaling, Jefri; Wawointana, Defie R.; Kalesaran, Ronald C.E. (Side: Scientific Development Journal, 2024)
Transportation in Indonesia plays a very important role in people's lives. Along with the development of the times, the transportation process as a means of transportation has developed and progressed. All of this has taken place since the development reform which is followed by the need for mass and cheap modes of transportation.  Trains are transportation that is chosen as a means of transportation that is able to transport goods and passengers in large quantities, free of obstacles and has a high level of security. The government built the Trans-Sulawesi railway line because the infrastructure will open regional access, bring production between regions to the exit of goods and services with a higher transport scale, accelerate the traffic of goods, increase accessibility, reduce production costs, make the production scale higher, and encourage comparative advantages of products, so that all of them can trigger regional economic development. Bitung City  is one of the cities included in the government program as a priority line for railway lines. Bitung City has a strategic area to facilitate the distribution of goods and services to various regions in East Asia so that transportation costs are also cheaper in contrast to through ports in other regions. Over the past few years, the government has determined to make Bitung the forefront of the economy with the determination of Bitung Port as an International Hub port and the existence of a Special Economic Zone. The government's move to develop Bitung as the front line of Indonesia's economy against the world market has attracted great attention from foreign countries. The design of the railway station in the city of Bitung is to provide land transportation facilities between cities and provinces with a safe and comfortable place for its users. The philosophy applied to the design of Class A Railway Station is an informal building. This informal nature comes from the main function of the design of the class A railway station in the city of Bitung, namely services that offer goods and services, so that it has an impact on the basic form of the building, namely informal. Based on the nature and type of activities, one of the right architectural concepts to be applied in the design of the Class A Railway Station in Bitung City is Contemporary Architecture.